Randomised controlled trial of zinc supplementation in malnourished Bangladeshi children with acute diarrhoea. Issue 3 (1st September 1997) - Roy, S K; Tomkins, A M; Akramuzzaman, S M; Behrens, R H; Haider, R; Mahalanabis, D; Fuchs, G
Abstract : OBJECTIVE: To evaluate the impact of zinc supplementation on the clinical course, stool weight, duration of diarrhoea, changes in serum zinc, and body weight gain of children with acute diarrhoea. DESIGN: Randomised double blind controlled trial. Children were assigned to receive zinc (20 mg elemental zinc per day) containing multivitamins or control group (zinc-free multivitamins) daily in three divided doses for two weeks. SETTING: A diarrhoeal disease hospital in Dhaka, Bangladesh. PATIENTS: 111 children, 3 to 24 months old, below 76% median weight for age of the National Center for Health Statistics standard with acute diarrhoea. Children with severe infection and/or oedema were excluded. MAIN OUTCOME MEASURES: Total diarrhoeal stool output, duration of diarrhoea, rate of weight gain, and changes in serum zinc levels after supplementation. RESULTS: Stool output was 28% less and duration 14% shorter in the zinc supplemented group than placebo (p = 0.06). There were reductions in median total diarrhoeal stool output among zinc supplemented subjects who were shorter (less than 95% height for age), 239 v 326 g/kg (p < 0.04), and who had a lower initial serum zinc (< 14 mmol/l), 279 v 329 g/kg (p < 0.05); a shortening of mean time to recovery occurred (4.7 v 6.2 days, p < 0.04) in those with lower serum zinc. There was an increase in mean serum zinc in the zinc supplemented group (+2.4 v −0.3 μmol/l, p < 0.001) during two weeks of supplementation, and better mean weight gain (120 v 30 g, p < 0.03) at the time of discharge from hospital. CONCLUSIONS: Zinc supplementation is a simple, acceptable, and affordable strategy which should be considered in the management of acute diarrhoea and in prevention of growth faltering in children specially those who are malnourished.